NURSING CARE ON THE TREATMENT AND TISSUE RECOVERING OF PATIENTS AFFECTED BY CUTANEOUS INJURIES : NURSING CARE ON THE TREATMENT AND TISSUE RECOVERING OF PATIENTS AFFECTED BY CUTANEOUS INJURIES - Silva, Damiana Gomes da; Freitas , Sergiany Mendes de; Bezerra , Yuri Charllub Pereira (Brazilian Journal of Production Engineering, 2020)
Introduction: Tissue injuries can potentially start damages and infections, especially when there are also joined morbities. The presence of the nurse is essential in the treatment, since they’re capable of acknowledging the necessities of the patients, delivering the application of the specialized conducts of their working area. However, it may be observed some resistance coming from certain services when it comes to the nurse’s autonomy, which furthers the stagnation of the system and stops a quality treatment. Objective: To analyze the nurse caring on the treatment and tissue recovering of patients affected by cutaneous injuries. Methods: Integrative review of literature, making use of the databases: Virtual Health Library (VHL), Latin American and Caribbean Literature on Health and Science (LILACS) and Scientific Electronic Library Online (SCIELO), from 2014-2019, full text and available in Portuguese. The keywords were: nurse, injuries, treatment and bandages, with the use of the Boolean operator “AND”. Results: Were identified 386 documents, after filtering only 40 were left. After analysis, some were also excluded for (title, text, duplicity, etc.), leaving only 06 articles left. Prevalence of researches that used descriptive/ quantitative methods. Conclusion: The nurse is essential to the maintaining of the integrity of the skin, being them the carrier of the technical and scientific knowledge necessary to deliver assistance to the tissue recovering. There are obstacles to this working class, being caused by scarce knowledge or difficulties in accomplishing its role, since the nursing class autonomy is, sometimes, not respected.
Keywords: Nurse; Injuries; Treatment; Bandages